The boundary of life and death: changes in mitochondrial and cytosolic proteomes associated with programmed cell death of Arabidopsis thaliana suspension culture cells - Schwarze, Johanna; Carolan, James C.; Stewart, Gavin S.; McCabe, Paul F.; Kacprzyk, Joanna (Frontiers in Plant Science, 2023)
Despite the critical role of programmed cell death (PCD) in plant development and defense responses, its regulation is not fully understood. It has been proposed that mitochondria may be important in the control of the early stages of plant PCD, but the details of this regulation are currently unknown. Here, we used Arabidopsis thaliana cell suspension culture, a model system that enables induction and precise monitoring of PCD rates, as well as chemical manipulation of this process to generate a quantitative profile of the alterations in mitochondrial and cytosolic proteomes associated with early stages of plant PCD induced by heat stress. The cells were subjected to PCD-inducing heat levels (10 min, 54oC), with/without the calcium channel inhibitor and PCD blocker LaCl3. The stress treatment was followed by separation of cytosolic and mitochondrial fractions and mass spectrometry-based proteome analysis. Heat stress induced rapid and extensive changes in protein abundance in both fractions, with release of mitochondrial proteins into the cytosol upon PCD induction. In our system, LaCl3 appeared to act downstream of cell death initiation signal, as it did not affect the release of mitochondrial proteins, but instead partially inhibited changes occurring in the cytosolic fraction, including upregulation of proteins with hydrolytic activity. Collectively, these generated data provide new insights into the regulation of cell death and survival decisions in plant cells.